Stock of Engineering and Technological Manpower in Maharashtra by 2000 A.D. - Bhandarkar, N. V. (Journal of Engineering Education Transformations, 1992)
While carrying out decennial population census, every household is given a seperate card for supplying the details of scientific&technical persons. On the, basis of the data thus collected, the Department of Science&Technology which is a user of this data, publishes them. The latest data is available upto 1981, taking it as a base an attempt is made to estimate number of degree and diploma holders in Maharashtra upto 2000 A. D. Even prior to starting of non-aided technical institutions, Maharashtra was leading in having highest percentage of degree and diploma holders in 1981 also as compared to other states in India. Alternative method used by the Planning Commission, Govt. of India, New Delhi is also attempted for estimating the stock of Engineers. This stock can be further refined by considering actual outturn. An attempt is also made to explain relationship between manpower and outturn, outturn and enrolment.